Pengaruh Konsentrasi Sari Buah Kurma (Phoenix dactylifer) terhadap Mutu Minuman Jeli Karika Kurma - Subagyo, Sabilla Haibati; Azni, Intan Nurul (Politeknik Negeri Lhokseumawe, 2023)
Karika is one of the typical fruits of Dieng, Wonosobo, Central Java. Karika has a high water content, so it is included in the fruit that does not last long when stored fresh. Characteristics of Karika fruit which is sour and slightly bitter and has sap that can cause itching, making Karika unpalatable to be consumed directly. To increase the usability of Karika fruit, food diversification is carried out by making Karika kurma jelly drink with the addition of Sukkari date juice as a sugar substitute sweetener. This study aims to examine the effect of the concentration of date palm juice (Phoenix dactylifera) on the quality of Karika kurma jelly drink. This type of research is an experimental study with a completely randomized design (CRD) with one factor and five levels of three repetitions. The data obtained were analyzed using ANOVA at level α 0.05 if there was a significant difference, then the Duncan Multiple Range Test (DMRT) was continued. The ANOVA test results showed that all parameters were significantly different. The more addition of the concentration of Sukkari date juice causes an increase in the value of viscosity, total dissolved solids, pH and total sucrose sugar, and decreases the value of syneresis. The results showed that the best treatment was the addition of 27.5% concentration of Sukkari date palm extract with a viscosity characteristic of 1204.67 Cps, total dissolved solids 8.53 (ºBrix), syneresis for 24, 48 and 72 hours respectively of 0 .18%, 0.32% and 0.52%, pH levels were 4.92, and sucrose levels were 2.93. The quality scores for color, aroma, taste and texture were 2.88 (dark yellow), 3.41 (rather strong), 3.19 (slightly sweet), and 2.81 (slightly chewy) with hedonic ratings like the parameters color, aroma, taste and texture.